A Rare Case of Drug-induced Vasculitis in Out-patient Department (Indian Journal of Case Reports, 2022)
Drug-induced vasculitis can be defined as inflammation of blood vessels triggered by a spectrum of drugs. It presents not only with a localized skin rash but also may involve the internal organ systems, including the gastrointestinal tract, kidneys, lungs, central nervous system, and joints. Here, we report the case of a 60-year-old woman who developed purpuric pruritic rashes on bilateral lower limbs and buttocks after the ingestion of sulphasalazine. The patient took the prescribed regimen for 14 days while experiencing an adverse drug reaction. At the follow-up visit, the patient was admitted and treated with methylprednisolone monotherapy with 32 mg/day for the first 3 days and after that, methylprednisolone 16 mg for the next 3 days. The rashes resolved after 6 days. Clinicians should ascertain the patient knowledge of how and when to obtain urgent care as the patient may experience ill effects after taking prescribed treatment. Timely advice may save patients’ costs of admission and treatment to manage adverse events.